Meant for each other : a literary-media studies approach to online fanfiction - VASWANI, SERENA (Archīum Ateneo, 2017)
In this study, I explore how fans relate to canonical storyworlds through online fanfiction by inductively analyzing the textual ecosystem of Klaine fans. I take a literary approach of looking at fantexts as narrative discourse relative to canon (Genette, 1972/1980; Genette, 1982/1997; Turk, 2011) and a media studies approach of looking at the wider contexts that invest them with meaning (Booth, 2016; Hills, 2002). Klaine fans take hold of telling Kurt and Blaine's story by changing their level within the structure of narrative communication and creating new storyworlds. They construct these by making use of various transtextual operations to transform the canon. The fan commentary that surrounds these storyworlds forms the meta-narrative discourse - the narrative of how these stories come to be written, read, and rewritten again. Fans are individual navigators who form communities in the digital realm - a medium that enables them to appreciate fanfiction both intratextually and intertextually.Two significant dialectics emerge from this. The write/read dialectic manifests in the way fans evaluate the writerly value of media texts. The art/object dialectic is manifested in fans' simultaneous recognition of Kurt and Blaine as both autonomous characters and intellectual property of the media producers.